The Yellow River Basin, Ecological Migration and Cultural Adaptation - Guorui Zhou, Zheng Gong, Yifang Fan & Liuji Gong (Journal of Dharma, 2025)
Contemporary Research indicates a clear convergence and exchange between ecological migration and cultural adaptation in the Yellow River Basin (YRB). The findings show that ecological restoration initiatives have effectively increased vegetation cover and improved soil stability. However, relocated communities continue to experience cultural and social disruptions. Despite these challenges, migrants have demonstrated resilience through adaptive cultural practices, interethnic cooperation and the preservation of traditional ecological knowledge. Participatory approaches appear vital, as they support both ecological success and cultural continuity, with governance emerging as the decisive factor. The study concludes that sustainable development in the YRB must balance ecological rehabilitation with cultural vitality, recognizing that human adaptation and environmental restoration are mutually reinforcing pillars of socio-ecological sustainability